2021
DOI: 10.3390/agronomy11102088
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Crop Rotations by Weed Management Strategies’ Interactions on Weed Infestation and Productivity of Wheat (Triticum aestivum L.)

Abstract: Weed infestations significantly reduce the growth and yield of field crops. Herbicides are mostly used for weed management due to their quick results. However, resistant biotypes to available herbicides are rapidly increasing around the word. This situation calls for the development of alternative weed management strategies. Crop rotation and allelopathic water extracts are regarded as the most important alternative weed management strategies. Therefore, this two-year study assessed the impact of different ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…These results are consistent with those of De Cauwer et al [38], who also indicated that false seedbed is a cultural practice for agroecological weed management that reduces weed biomass at harvest. In another recent study conducted on wheat (Triticum aestivum L.), Shahzad et al [39] found that a false seedbed significantly reduced weed density and biomass compared to conventional seedbed manipulations.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of De Cauwer et al [38], who also indicated that false seedbed is a cultural practice for agroecological weed management that reduces weed biomass at harvest. In another recent study conducted on wheat (Triticum aestivum L.), Shahzad et al [39] found that a false seedbed significantly reduced weed density and biomass compared to conventional seedbed manipulations.…”
Section: Discussionmentioning
confidence: 99%
“…Crop rotation introduces conditions and methods that are undesirable for a particular weed species, preventing its development and reproduction. Rice-wheat crop rotation had higher weed density, while sorghum-wheat rotation reduced weed density and biomass (Shahzad et al, 2021). Summer crops added to wheat-based crop rotations have been shown to reduce the density of blackgrass by up to 99% (Zeller et al, 2021).…”
Section: Crop Rotationmentioning
confidence: 99%
“…Resistant weeds and pests are a significant challenge in modern agriculture. To effectively manage these issues, farmers should employ a combination of control methods, including rotational cropping [88,89], biological control [90,91], and integrated pest management [92,93]. Crop rotation involves growing different crops in a field during different seasons, which can help to reduce the buildup of pests and weeds [83].…”
Section: Loss Due To Weeds and Pestsmentioning
confidence: 99%